1981
DOI: 10.1210/jcem-52-4-678
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Release and Plasma Anterior Pituitary and Gonadal Hormones in Women during Lactation*

Abstract: Serial plasma oxytocin (OT), PRL, TSH, FSH, LH, estrone, estradiol, and progesterone were measured by RIA in 12 women before and during a 30-min breast-feeding period on the third or fifth postpartum day. Plasma OT increased significantly from 10.8 +/- 3.4 to 22.4 +/- 3.5 pg/ml (mean +/- SE) within 2 min of suckling (P = less than 0.05) to reach the mean peak level of 53.2 pg/ml at 10 min. The increase in plasma OT was bimodal. Plasma PRL and TSH also increased significantly from baseline levels of 192 +/- 39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 25 publications
10
53
1
Order By: Relevance
“…It is thought that oxytocin is more diluted in milk because milk secretion increases day by day. The effect of suckling on oxytocin concentrations in milk is similar to that seen in blood (Weitzman et al, 1980;Dawood et al, 1981), and in rat dams, the administered 3H-oxytocin is transferred to milk. It is suggested that oxytocin can be transferred from blood into milk in humans.…”
Section: Methodssupporting
confidence: 57%
“…It is thought that oxytocin is more diluted in milk because milk secretion increases day by day. The effect of suckling on oxytocin concentrations in milk is similar to that seen in blood (Weitzman et al, 1980;Dawood et al, 1981), and in rat dams, the administered 3H-oxytocin is transferred to milk. It is suggested that oxytocin can be transferred from blood into milk in humans.…”
Section: Methodssupporting
confidence: 57%
“…Oxytocin spikes in the maternal circulation within a few minutes of the baby being put to the breast (230,655). C) SUMMARY.…”
Section: Sex Steroids and Other Hormonesmentioning
confidence: 99%
“…It acts on a G protein-coupled receptor (Oxtr), the expression of which in reproductive tissues is regulated by sex steroids and OT. In humans and rodents, plasma OT levels are elevated maximally during suckling (1,2).…”
mentioning
confidence: 99%